Incidence of carcinoma of the uterine body at the NIE - Valdivia Ponce, Eduardo (2015)
From july 1952 to december 1954 we have attended in the I.N.E.N. 1,041 patients with carcinoma of the uterus, of which 1,005 belong to the cervix and 36 to the body. It gives us a rate of 1 carcinoma of the body for 30 of the cervix. The vaginal smear, as diagnostic procedure, was accurate in the 48.27%, which has a low incidence of accuracy. The smear procedure is a good aid for diagnosis when it considers : 1) exocervical, 2) endocervical and 3) endometrial smear. Many kinds of implements can help us to get the smear without disturbance for the patient, (Clamps, applicators, pipets, spatulas, brushes, polietilene tubes, etc., etc.). It is recommended that the smear must always be confirmed by the biopsy before any treatment.